2010
DOI: 10.1021/ma102267f
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Enhancement of Superacid-Catalyzed Polyhydroxyalkylation Reactions

Abstract: Complementary theoretical and experimental studies of the consecutive steps of superacid catalyzed polyhydroxyalkylation reactions have been carried out. Calculations for the superacid catalyzed polyhydroxyalkylation of trifluoroacetone and trifluoroacetophenone with aromatic hydrocarbons explained a number of experimental facts within a single theoretical framework of monoprotonation. The principal factors affecting kinetics of superacid mediated hydroxyalkylation were shown to be as follows: (i) the acidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 36 publications
2
91
0
Order By: Relevance
“…37 Because the rst step is rate-determining, the presence of a small excess of the ketone monomers dramatically enhances the polymerisation rate and the molecular weight of the resulting polymers. 36,38 However, using too large excess of ketones may instead lead to crosslinking and gelation. 38 Consequently, we used an excess of the ketones corresponding to 10-15 mol% of the biphenyl in the present copolycondensation.…”
Section: Polymer Synthesis and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Because the rst step is rate-determining, the presence of a small excess of the ketone monomers dramatically enhances the polymerisation rate and the molecular weight of the resulting polymers. 36,38 However, using too large excess of ketones may instead lead to crosslinking and gelation. 38 Consequently, we used an excess of the ketones corresponding to 10-15 mol% of the biphenyl in the present copolycondensation.…”
Section: Polymer Synthesis and Characterisationmentioning
confidence: 99%
“…36,38 However, using too large excess of ketones may instead lead to crosslinking and gelation. 38 Consequently, we used an excess of the ketones corresponding to 10-15 mol% of the biphenyl in the present copolycondensation. The resulting precursor copolymers containing TFAp and TFAc residues are denoted as PBPmPh and PBPmMe, respectively, where m indicates the mol% of biphenyl piperidine units, as calculated from 1 H NMR spectra ( Fig.…”
Section: Polymer Synthesis and Characterisationmentioning
confidence: 99%
“…Superacid polymerization products have high molecular weight without moisture but are easily crosslinked due to the high reactivity [25]. The nickel-catalyzed coupling reaction is more sensitive to moisture than the acid reaction but it is possible to have stable reaction products with high molecular weight.…”
Section: Preparation Of the Polymersmentioning
confidence: 99%
“…Such an interaction of these cations can only exist in a superacid medium, resulting in extremely reactive dication species in the condensed state. Olah et al 98 and Shudo and colleagues 99 suggested that a similar dication intermediate was predominant in the Friedel-Crafts reaction of the carbonyl compound with benzene in a superacid, although Fomine and colleagues 109 and Zolotukhin and colleagues 110 proposed a different mechanism by calculation, resulting in only the monocation intermediate without the formation of a dication. On the basis of Olah's proposal, in addition to the results of the model reaction between 2,2,2-trifluoroacetophenone and anisole in TFSA, the mechanism is postulated as shown in Scheme 22(a), in which the diprotonated carbonyl compound in a superacid condenses with anisole to yield an intermediate monocation compound, the reactivity of which is lower than that of the dication.…”
Section: Linear Polymers Derived From Ab 2 Monomersmentioning
confidence: 99%